The Impact of Fatherless in the Ability to Control Self-Emotions in Children - Utami, Nurfallah Dwi; Rakhmat, Cece; Zulkarnaen, Rizki Hadiwijaya (CV. Rayyan Dwi Bharata, 2023)
In the development of children, the role of a father is very important. In addition to being the head of the family, the father figure is a protector for the child. Fathers are expected to be protectors and givers of security. The absence of a father figure will have an impact on the child's personality and psychological condition. It can also affect other aspects of the child, especially problems controlling emotions. This condition is then referred to as fatherless. Indonesia currently ranks 3rd as a fatherless country. Using a qualitative approach, this study aims to describe how fatherless impacts children's emotions. The research was conducted at Bagja Mandiri Housing, Tasikmalaya City. Data collection techniques using observation, interviews, and documentation studies. The key informants in this study were 3 children who experienced fatherlessness. The criteria used are divorced, divorced and dead, and the physical absence of the father. The results of the study revealed that the emotions that arise due to fatherlessness are self-harm, lingering sadness, and the compulsion to become independent individuals.